IMPLEMENTASI REFORMASI BIROKRASI DAN PELAYANAN INVESTASI PADA DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU PROVINSI JAWA TENGAH INDONESIA: Implementasi Reformasi Birokrasi dan Pelayanan Investasi Pada Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu - Enceng, Enceng; Purwaningdyah, Purwaningdyah; Ismiyarto, Ismiyarto (Fakultas Hukum Universitas Jambi, 2023)
Public service from upstream to downstream is filled with friendship, ethnicity, and political affiliation. It is common knowledge that the public service process, including investment services, is greatly influenced by who gets what in which relationship. The public service process does not have transparency in terms of time, costs, and procedures that must be followed, resulting in complicated procedures and quite high costs. Licensing procedures involving central authority are difficult to issue quickly in a simple process. Regulatory uncertainty is part of bad governance, this challenge must be overcome so that investors are attracted to Indonesia. Investors are not interested in entering Indonesia but have difficulty realizing their investment. The problem is not as easy as turning the palm of the hand to make the investment climate in Indonesia attract investors. Issues related to ease of licensing, overlapping laws and regulations, and regulations that are out of sync are still often heard. The concept of one-stop integrated services to electronically integrated business licensing has been echoed. For this reason, reforming business licensing and regulations is a national priority agenda, the government is committed to providing legal certainty for investors and business actors. This is one method of bureaucratic reform, namely